NUMERICAL SIMULATION OF GFRP AND CFRP AS RADAR ABSORBING MATERIALS IN TESTING USING RECTANGULAR WAVEGUIDE METHOD - Michail
The use of composite materials in the world of aviation has been applied for a long time such as in the world of military vehicles. Composites provide advantages in the form of light and strong as well as characteristics in absorbing the emitted radar waves so that the process of carrying out a secret mission can be carried out without being detected. Therefore, it is necessary to research the parameters that affect the absorption properties of radar waves on composite materials. This study aims to model a material that has characteristics as a Radar Absorbing Material (RAM) in the X-band frequency range using Glass Fiber Reinforced Polymer (GFRP) and Carbon Fiber Reinforced Polymer (CFRP) materials. The modeling is done using Altair FEKO software. The modeling uses data obtained from experiments using the rectangular waveguide method. The value of the S-parameter numerical simulation results will then be compared with the results obtained from the experiment. The parametric studies studied and varied the parameters of thickness, density, and thickness of the dielectric layer of the specimen. Based on the simulations that have been carried out, it is obtained that the thickness of the material affects the radar wave absorption properties of a specimen.